Haematological values ​​in healthy men and women residing in Arequipa - Torres Portugal, Manuel (1959)
We have studied some hematologic determinations 90 men and 80 apparently healthy residents and natives of the city of Arequipa, corresponding to an average height of 2,327 meters above sea level women. The results obtained were subjected to statistical analysis, comparing the values ​​found at sea level and in other parts of the world.